Optimization of subcritical water pre-treatment for biogas enhancement on co-digestion of pineapple waste and cow dung using the response surface methodology - Aili Hamzah, A. F.; Hamzah, M. H.; Mazlan, N. I.; Che Man, H.; Jamali, N. S.; Siajam, S. I.; Show, P. L. (Elsevier, 2022)
The optimal pre-treatment method and conditions depend on the types of lignocellulose present due to the complexity and the variability of biomass chemical structures. This study optimized subcritical water pre-treatment to ensure maximum methane production from pineapple waste prior to anaerobic co-digestion with cow dung using the response surface methodology. A central composite design was achieved with three different factors and one response. A total of 20 pre-treatment runs were performed at different temperatures, reaction times and water to solid ratios suggesting optimum values for subcritical water pre-treatment at 128.52℃ for 5 min with 5.67 to 1 water to solid ratio. Under these conditions, methane yield increased from 59.09 to 85.05 mL CH4/g VS with an increase of 23% biogas yield and 44% methane yield from the untreated. All pre-treatments above 200℃ showed reductions in biogas yield. Compositional analysis showed slight reduction of lignin and increase in α-cellulose content after the pre-treatment. Analysis using Fourier transform infrared spectroscopy and thermogravimetric analysis verified the presence of cellulosic material in pre-treated pineapple waste. Most of the hemicellulose was solubilized in the liquid samples after SCW pre-treatment. The crystallinity index of pineapple waste was reduced from 57.58% (untreated) to 54.29% (pre-treated). Scanning electron microscopy confirmed the structural modification of pre-treated pineapple waste for better microbial attack. Subcritical water pre-treatment is feasible as a promising method to enhance the anaerobic co-digestion process. Further study should be conducted to assess the scale-up of the process from pre-treatment to anaerobic digestion at the pilot plant level.